Intuition and Reason: Re-Assessing Dual-Process Theories with Representational Sub-Activation. - Trafford, James; Tillas, Alexandros (Teorema)
There is a prevalent distinction in the literature on reasoning, between Type-1 processes (fast, automatic, associative, heuristic and intuitive); and Type-2 processes (rulebased, analytical and reflective). In this paper, we follow up recent empirical evidence [De Neys (2006b); Osman (2013)] in favour of a unitary cognitive system. More specifically, we suggest that intuitions (T1-processes) are sub-activated representations, which are in turn influenced by the weightings of the connections between different representations. Furthermore, we explain biases by appealing to the role of attention in thinking processes. The suggested view explains reasoning and bias whilst dealing with extant problems facing dual-process accounts.